Effect of Different Sugars on Shoot Induction in CV. Basmati - Thapa, Ruby; Dhakal, Dipesh; Gauchan, Dhurba Prasad (Kathmandu University Journal of Science, Engineering and Technology, 2007)
Effect of various concentrations of different sugars was investigated for induction of root and shoot from basmati rice. Explant, seeds (grains) were transferred in ½ MS basal media fortified with different concentrations of carbon source like sucrose, maltose, and dextrose. In vitro regenerated rice plantlets were healthy and attained a length of 16.17cm at 0.25 % concentration within a week. Only low concentration (0.25%) of dextrose exhibited the maximum shoot and root growth, out of three sugars. Maltose showed the moderate growth response of shoot and root length in all the concentrations.